Factors Influencing Farmers’ Decision Making in Organic Rice Cultivation at Al-Barokah Gapoktan, Lombuk Kulon Village, Wonosari District, Bondowoso Regency - Romadi, Ugik; Adiyanto, Firman; Rahmi, Ainu (Jurnal Penyuluhan Pertanian, 2023)
The demand for organic rice products in the Al Barokah Gapoktan until 2021 reaches 520 tons/year, while the availability of raw materials is only 430 tons/year. So it is necessary to expand the land and recruit organic farmers. This study aims to find factors that influence the decision making of organic rice cultivation in the Al Barokah Gapoktan, Bondowoso Regency. This research is a descriptive quantitative study, with interview data collection techniques through questionnaires to 76 samples taken through simple random sampling. The data is then processed and analyzed using multiple linear regression data analysis. The results of the analysis of the data obtained, the availability of services (farm credit, facilities & infrastructure, marketing guarantees) and the nature of innovation (relative profit, compatibility, complexity and observability) have a significant effect on decision making in organic rice cultivation. Meanwhile, the characteristics of farmers (age, education, intensity of attending counseling, land area and income) did not significantly influence the decision making of organic rice cultivation.